CLIENT SATISFACTION AND WAITING TIME IN MCH EMERGENCY - ZAFAR , M; MAZHAR , SB; SEHAR , T; AINY, .; MUMTAZ , A; BANO , N; USMAN , Z (Biological and Clinical Sciences Research Journal, 2023)
The emergency departments are often a source of complaints. Due to the COVID-19 pandemic, we are facing an increase in the number of patients in MCH ER. The patients are referred from all over the country, which increases the burden on the facility compared to the available resources. The department has to face the burden of non-booked patients secondary to the COVID-19 pandemic presenting to the MCH ER, leading to increased complaints about client dissatisfaction regarding the Emergency department. Hence, we decided to audit our current ER and plan interventions to improve our practices. We propose to formulate recommendations for other facilities facing similar challenges. This study aimed to determine the waiting time and total length of stay in the mother and child health care emergency of the Pakistan Institute of Medical Sciences to plan interventions to reduce client dissatisfaction. An audit study was conducted from 1st September 2021 to 30th September 2021, and then a re-audit with interventions was carried out from 1st April 2022 to 30th April 2022 at the Emergency of Mother and Child Health and Care Center of Pakistan Institute of Medical Sciences. The Study had the active participation of duty doctors, nurses, paramedics, statisticians, computer operators, personnel from HMIS, workers, and patients. This study was conducted to determine our practices in an emergency. The data was collected from maintained existing paper-based doctors' and staff nurses’ registers. The duty doctor manually enlisted patient’s data on worksheets, this data was then shared in the "MCH ER WhatsApp group" and compiled. The data was entered on SPSS 25 and analyzed. Primary Outcome measures were waiting time for assessment, primary (registration to triage time), secondary assessment (triage to decision time), and total length of stay in ER (Door to deposition time). Secondary outcome measures included client dissatisfaction rate. A total of 1447 patients were included, of which 46 % were from Islamabad and 38% were from Rawalpindi. The first assessment by a duty ER doctor within 5 minutes (registration to triage time) was 16.4%, which increased to 25.5%, and 59.2% at 30 minutes, which increased to 70.7% in the re-audit. The second assessment by senior (doctor to decision time) within 30 minutes was 59% and increased to 69% in re-audit. Admissions were offered to 33.6%, 1.1% left against medical advice (LAMA), and 38 % were lost to follow-up. The total length of stay in MCH ER (Door to deposition time) was 3 hours mean (195 min) in 60% of the patients (37.9% of patients were admitted, 22.1% were discharged). In the re-audit, 69.6% were admitted after interventions, 27.6% were discharged (97% door to deposition time within 3 hours with a (mean time of 180 min ), 1.8% LAMA and only 1% were lost to follow-up. Both study cycles had no significant change in CTGs, ultrasounds, or baseline investigation frequency. Complaints can be curtailed by taking measures such as adding another duty doctor in emergency for immediate triage, early second assessment by seniors to shorten the triage to decision time, and avoiding unnecessary ultrasounds and baseline investigations. The most significant determinant of client satisfaction in the ER is the short length of Stay in the ER that is, arrival to deposition time.